Pandemic - Cook, Robin, 1940- (G.P. Putnam's Sons, 2018)
"The explosive new medical thriller from New York Times-bestselling author Robin Cook. After a young, seemingly healthy woman collapses suddenly on the NYC subway and dies by the time she reaches the hospital, her case is initially chalked up to a virulent strain of influenza. That is, until she ends up on Dr. Jack Stapleton's autopsy table, where Jack discovers something eerily fishy: First, that the young woman has had a heart transplant, and second, that her DNA matches that of the transplanted heart. Strangely, two more incidences of young people with this same sudden and rapid illness follow, and Jack fears that this could be the start of an unprecedented pandemic. But the facts aren't adding up. Something is off about these cases, something creepy, and only Jack can figure it out before it's too late. Thus begins a race against time, during which Jack unveils the dark underbelly of the organ-transplant market. His name is Bui Zhao, a businessman and hospital board member who has been cheating the system by using organs and cells from chimeric pigs, via the gene-editing biotechnology CRISPER/CAS9, which allows pig genes to be inserted into living human cells. In a climactic mortal showdown, Jack must face Zhao, the megalomaniac willing to risk the fate of the world to purse his commercial interests, if he wants to save the future of medicine"--